Skill-based differences in the impact of opponent exposure during anticipation: the role of context-environment dependency - Gredin, N. Viktor; Thomas, Joseph L.; Broadbent, David P.; Fawver, Bradley; Williams, A. Mark (Frontiers in Cognition, 2023)
Introduction We examined skilled-based differences in the impact of exposure to an opponent with action tendencies that were either independent of, dependent on, or both independent of and dependent on evolving environmental information during anticipation. Methods A video-based two-vs.-two soccer task was employed, where 14 expert and 14 novice soccer players had to predict an attacking opponent's imminent actions, before and after exposure to the preceding actions of the opponent. Results Anticipation accuracy, number of responses congruent with the opponent's action tendencies, response confidence, and visual dwell time on the opponent in possession increased following opponent exposure, both in experts and novices. When compared to novices, experts demonstrated higher anticipation accuracy, more congruent responses, and greater response confidence. Novices performed at their best when the opponent exhibited action tendencies that were independent of the environment, whereas experts demonstrated their highest performance when the opponent had action tendencies that were both independent of and dependent on unfolding environmental information. Discussion Our findings provide novel insights into the role of context-environment dependency and support the notion that experts are superior to novices in detecting and utilizing opponents' action tendencies and integrating this information with unfolding environmental information during anticipation.